Enhancement of Natural Rubber (Hevea brasiliensis Muell. Arg) Yield Through TSP and KCL Fertilization in Smallholder Rubber Plantations of Binuang Village: Peningkatan Produksi Karet Alam (Hevea brasiliensis Muell. Arg) Melalui Pemupukan TSP dan KCL Kebun Karet Rakyat Desa Binuang - Akhmad Sopian; Listher Mada Rannu; Mahdalena (Universitas Widya Gama Mahakam, 2025)
Suboptimal soil conditions can lead to reduced latex production and quality. One of the main factors influencing latex production is soil fertility, where fertile soil with adequate nutrient content can enhance latex yield. One of the efforts to improve production is through proper fertilization, where the dosage and timing of phosphorus (P) and potassium (K) application must align with the needs of the rubber plant and the condition of the soil. By using appropriate P and K fertilizers, rubber farmers can increase both latex yield and quality. This research was conducted using a factorial experiment with a randomized complete block design (RCBD) and three replications. The first factor was the amount of TSP fertilizer, divided into four categories: P0 = without TSP application per tree, P1 = 175 g per tree, P2 = 200 g per tree, and P3 = 225 g per tree. The second factor was the dose of KCl fertilizer, consisting of four categories: K0 = control, K1 = 200 g per tree, K2 = 250 g per tree, and K3 = 300 g per tree. The findings indicated that TSP fertilizer application had a significant effect on dry rubber content, while KCl doses did not show a significant effect on latex volume, wet latex weight, dry latex weight, or dry rubber content. Keywords: Hevea brasiliensis, latex production, phosphorus, potassium